Kajian Awal Antropometri Postur Berdiri Pekerja Pria Indonesia yang Berdomisili di Jakarta - Servianus , Yohanes Viva; Yanto (Cylinder : Jurnal Ilmiah Teknik Mesin, 2023)
This paper presents a preliminary result of anthropometric data of 30 males Indonesian industry workers. For this preliminary results, 16 dimensions in the standing posture were presented. For each dimension, the summary of mean, SD and percentile (5 and 95) were calcaluted which are useful as the basis for the design of products, machines and equipments. The data in this study were compared with those from previous studies i.e Norwegia, Nigeria and India. From data comparisons, Indonesian workers are shorter than those of other nationalities from Norwegia and Nigeria. Meanwhile, anthropometric characteristics of Indonesian workers were found to be similar with India workers. As for application, anthropometric data could be used as the basis to determine the proper dimensions of equipments and machines to be used by workers. Furthermore, the results could become a benchmark for other countries targeting products and machinery for Indonesia market.